Exploring the Practices on Macro Skills Integrated Assessment in Philippine Higher Education Context:Basis in Designing a Language Training Material - Raymundo, Jennelyn Lacar (Universitas Negeri Makassar, 2023)
Despite the great number of studies on separated skills assessment in measuring language performance, integrated assessment has recently been occupying a significant place as educational paradigm shift continues to uphold a more skills-oriented language assessment scheme. This research determined the practices on integrated assessment of macro skills in English as a Second Language (ESL) classes to subsequently design a Language Training Program (LTP) and material appropriate to teachers’ needs. It followed the design of a Type I developmental research which includes multilevel stages of instructional development such as analysis, design, implementation and evaluation. Nevertheless, this paper only reports the analysis phase of the research due to its longitudinal nature and the multifaceted analysis of the qualitative data. It utilized interview and document analysis as initial research instruments. The participants of the study were language teachers and learners selected via total enumeration and purposive sampling, respectively. As a result, the research accentuates the need to improve the employment of stimulus-related and thematically linked tasks as equally significant features defining the practice of integrated assessment in language classrooms.